A metamorfose do trabalho: direitos informais , deveres escravos - Amador, Solange Monteiro (2014)
This thesis focuses on the work category in the Brazilian production and social reproduction. This category was examined through the prism of Bolivian immigrants, workers and residents in the sewing factories in the city of São Paulo, in order to understand the modern slave labor. The research, both theoretical and empirical, consists on the study of references about the Brazilian historical process, highlighting the debate over the slave and free labor, the implementation of neoliberal ideology, the flexibility of labor, the expansion of informal work, the repetition on forms of organization and labor relations and the resulting deregulation of rights, beyond the perpetuation of slave labor. The productive restructuring in the textile garment sector enables the Bolivian legal and illegal immigration, encouraged by the demand for labor in the sewing garages, forming the modern slave labor. The research relies on interviews with four Bolivians who work in sewing shops in the city of São Paulo, one of whom, owner of the garage. The display of the results of field research supports all bibliographic review, focusing on the concrete social process. São Paulo registered 17.960 Bolivians living in the city in 2013. This number represents an increase of 173 % since 2000 and puts the Bolivian immigrant colony in second position in the city, whose leadership is Portuguese. Many Bolivians who live and work in sewing garages in the central districts of São Paulo city are part of the 21 million slave laborers in 2013 around the world. This manpower army generated a profit to the private economy about 330 billion reais according to the ILO, which also revealed this amount as twice the value generated by the international drug dealing. Slavery abolished in Brazil in 1888 with the Golden Law reveals itself under a new guise, positioning the work category at the center of debate